Study of the fluorescence and interaction between cyclodextrins and neochlorogenic acid, in comparison with chlorogenic acid - Silvia Navarro-Orcajada; Adrián Matencio; Cristina Vicente-Herrero; Francisco García-Carmona; José Manuel López-Nicolás (Scientific Reports, 2021)
Abstract Neochlorogenic acid, a less-studied isomer of chlorogenic acid, has been seen to posses antioxidant, antifungal, anti-inflammatory and anticarcinogenic effects, which makes it an interesting candidate for incorporation in functional foods. However, its poor solubility in water and susceptibility to oxidation make such a task difficult. To overcome that, its encapsulation in cyclodextrins (CDs) is proposed. The fluorescence of neochlorogenic acid in different pH conditions was analyzed, and caffeic acid was proved to be the fluorescent moiety in the molecule. An encapsulation model whereby the ligand poses two potential complexation sites (caffeic and D-(-)-quinic moieties), showed that α-CD and HP-β-CD formed the best inclusion complexes with neochlorogenic acid, followed by M-β-CD, β-CD and γ-CD. Molecular docking with the two best CDs gave better scores for α-CD, despite HP-β-CD providing stabilization through H-bonds. The encapsulation of chlorogenic acid led to a similar CD order and scores, although constants were higher for α-CD, β-CD and M-β-CD, lower for HP-β-CD, and negligible for γ-CD. The protonation state affected these results leading to a different order of CD preference. The solubility and the susceptibility to oxidation of neochlorogenic acid improved after complexation with α-CD and HP-β-CD, while the antioxidant activity of both isomers was maintained.